2000
DOI: 10.1034/j.1600-0773.2000.d01-79.x
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-Emodin Quinone Pretreatment Reduces Acute Liver Injury Induced by Carbon Tetrachloride

Abstract: Aloe contains several active compounds including aloin, a C-glycoside that can be hydrolyzed in the gut to form aloe-emodin anthrone which, in turn, is auto-oxidized to the quinone aloe-emodin. On the basis of the claimed hepatoprotective activity of some antraquinones, we studied aloe-emodin in a rat model of carbon tetrachloride (CCl4) intoxication, since this xenobiotic induces acute liver damage by lipid peroxidation subsequent to free radical production. Twelve rats were treated with CCl4 (3 mg/kg) intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 29 publications
(30 reference statements)
0
60
0
Order By: Relevance
“…Preliminary phytochemical studies showed the presence of tannins, saponins, flavonoids, terpenoids, cardiac glycosides and alkaloids. Hepatoprotective action is found in cinnamic acid (Simonyan, 1993), ferulic acid (Srinivasan et al, 2007), saponins, (Kumar et al, 2011;Gujrati et al, 2007), syringic acid (Itoh et al, 2009) alkaloids (Gujrati et al, 2007;Vijayan et al, 2003), vinillin (Makni et al, 2011), tannins (Sathaya et al, 2011, anthraquinones (Arosio et al, 2008) and flavonoids (Vijay and Padmaa, 2011;Sahreen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary phytochemical studies showed the presence of tannins, saponins, flavonoids, terpenoids, cardiac glycosides and alkaloids. Hepatoprotective action is found in cinnamic acid (Simonyan, 1993), ferulic acid (Srinivasan et al, 2007), saponins, (Kumar et al, 2011;Gujrati et al, 2007), syringic acid (Itoh et al, 2009) alkaloids (Gujrati et al, 2007;Vijayan et al, 2003), vinillin (Makni et al, 2011), tannins (Sathaya et al, 2011, anthraquinones (Arosio et al, 2008) and flavonoids (Vijay and Padmaa, 2011;Sahreen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acute CCl 4 administration is another widely used model of drug-induced hepatotoxicity (Arosio et al ., 2000;Yamazaki et al ., 2005;Dwivedi et al ., 2006). In this case, we observed that both wild-type ( n = 7) and Little ( n = 5) mice showed extensive liver damage.…”
Section: Carbon Tetrachloride Experimentsmentioning
confidence: 99%
“…As a natural bioactive anthraquinone, emodin has previously been used therapeutically to treat gastroenteric and liver diseases (21). Emodin is widely used for multiple effects, such as antiviral and hepatoprotective activities (22,23); however, current studies focus more on the anti-tumor activity of emodin. Previously, emodin was demonstrated to inhibit breast cancer cell growth (24).…”
Section: Discussionmentioning
confidence: 99%